KEMAMPUAN KETERAMPILAN SOSIAL SISWA DALAM PEMBELAJARAN FISIKA MELALUI PENERAPAN COOPERATIVE LEARNING TEKNIK SOLO DI KELAS XI IPS3 SMAN 12 PEKANBARU - Yanti, Lili; M.Rahmad, M.Rahmad; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this research is to describe the ability of student’s social skills in class XI IPS3 SMAN 12 Pekanbaru through the application cooperative learning SOLO techniques on material impulse, momentum, and collision. The design was pre-experimental with the one-shot case study. The research subject were students of class XI IPS3 that consist of 31 students, 10 male students and 21 female students. Data were obtained from the observastion of student’s social skills. The result of this research showed the improvement of shows in crease the ability of student’s social skills . The improvement occuof through the aplication of cooperative learning SOLO techniques. The increase accurred in every indicators of student’s social skills as: active listening; Pose the questions; Take turn in sharing the task; cooperative (mutual cooperative); and tolerance. The results showed that acquisition value the average percentage for all indicators of student’s social skills in the middle category. Therefore, it can be concluded that aplication of cooperative learning SOLO techniques able to train of student’s social skills in class XI IPS3 SMAN 12 Pekanbaru.Keywords: student’s social skill, cooperative learning, SOLO techniques, momentum impulse and collision.